Current challenges and future directions for engineering extracellular vesicles for heart, lung, blood and sleep diseases. Issue 2 (12th February 2023) - Li, Guoping; Chen, Tianji; Dahlman, James; Eniola‐Adefeso, Lola; Ghiran, Ionita C.; Kurre, Peter; Lam, Wilbur A.; Lang, Jennifer K.; Marbán, Eduardo; Martín, Pilar; Momma, Stefan; Moos, Malcolm; et al.
Abstract: Extracellular vesicles (EVs) carry diverse bioactive components including nucleic acids, proteins, lipids and metabolites that play versatile roles in intercellular and interorgan communication. The capability to modulate their stability, tissue‐specific targeting and cargo render EVs as promising nanotherapeutics for treating heart, lung, blood and sleep (HLBS) diseases. However, current limitations in large‐scale manufacturing of therapeutic‐grade EVs, and knowledge gaps in EV biogenesis and heterogeneity pose significant challenges in their clinical application as diagnostics or therapeutics for HLBS diseases. To address these challenges, a strategic workshop with multidisciplinary experts in EV biology and U.S. Food and Drug Administration (USFDA) officials was convened by the National Heart, Lung and Blood Institute. The presentations and discussions were focused on summarizing the current state of science and technology for engineering therapeutic EVs for HLBS diseases, identifying critical knowledge gaps and regulatory challenges and suggesting potential solutions to promulgate translation of therapeutic EVs to the clinic. Benchmarks to meet the critical quality attributes set by the USFDA for other cell‐based therapeutics were discussed. Development of novel strategies and approaches for scaling‐up EV production and the quality control/quality analysis (QC/QA) of EV‐based therapeutics were recognized as the necessary milestones for future investigations.